A conversation with David Anderson. - Maurer, Jim (New York ACM, 2005)
Supercomputing on the grassroots level
Keywords: General Literature; Miscellaneous; Computer systems organization; Computer communication networks; Distributed systems; Distributed applications; Information systems; Information storage and retrieval; Systems and software; Computing Milieux; Computers and society; Social issues; Personal computing